Separating stimulus-driven and response-related LRP components with Residue Iteration Decomposition (RIDE). - Stürmer, B; Ouyang, G; Zhou, C; Boldt, A; Sommer, W (2013)
When the lateralized readiness potential (LRP) is recorded in stimulus-response compatibility (SRC) tasks, two processes may overlap in the LRP, stimulus-driven response priming and activation based on response selection rules. These overlapping processes are hard to disentangle with standard analytical tools. Here, we show that Residue Iteration Decomposition (RIDE), based on latency variability, separates the overlapping LRP components from a Simon task into stimulus-driven and response-related components. SRC affected LRP amplitudes only in the stimulus-driven component, whereas LRP onsets were affected only in the response-locked component. Importantly, the compatibility effect in reaction times was more similar to the effect in the onsets of the RIDE-derived response-locked LRP component than in the unseparated LRP. Thus, RIDE-separated LRP components are devoid of distortions inherent to standard LRPs.